P‐64: Ultra‐Uniform Oblong Integrating Light Source. Issue 1 (May 2016) - Kelley, Edward F.; Dowd, Austin; Fong, Alex; Bronson, Bob; Goodman, Will
Abstract : Many small uniform sources are integrating spheres often with a 1 % nonuniformity. By placing a cylindrical element between the two hemispheres we were able to reduce the nonuniformity to approximately 0.1 %. This makes such a calibration source much less sensitive to detector measurement‐field size at the exit port.